2013
DOI: 10.1093/infdis/jit390
|View full text |Cite
|
Sign up to set email alerts
|

Undisclosed Antiretroviral Drug Use in a Multinational Clinical Trial (HIV Prevention Trials Network 052)

Abstract: The HIV Prevention Trials Network 052 study enrolled serodiscordant couples. Index participants infected with human immunodeficiency virus reported no prior antiretroviral (ARV) treatment at enrollment. ARV drug testing was performed retrospectively using enrollment samples from a subset of index participants. ARV drugs were detected in 45 of 96 participants (46.9%) with an undetectable viral load, 2 of 48 (4.2%) with a low viral load, and 1 of 65 (1.5%) with a high viral load (P < .0001); they were also detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 9 publications
(12 reference statements)
6
71
3
Order By: Relevance
“…There are many reasons pre-ART individuals may present as aviraemic. A detailed discussion of this phenomenon is beyond the scope of this article, but undisclosed ART use dispensed from a different facility and transient virological control are just two common causes that may confound the use of VL as a confirmatory tool [1920]. In these aviraemic individuals, further serological testing is required, but our calculation suggests that this tandem VL-ELISA approach is 10 times more costly than simply confirming every positive RDT with ELISA alone.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reasons pre-ART individuals may present as aviraemic. A detailed discussion of this phenomenon is beyond the scope of this article, but undisclosed ART use dispensed from a different facility and transient virological control are just two common causes that may confound the use of VL as a confirmatory tool [1920]. In these aviraemic individuals, further serological testing is required, but our calculation suggests that this tandem VL-ELISA approach is 10 times more costly than simply confirming every positive RDT with ELISA alone.…”
Section: Resultsmentioning
confidence: 99%
“…Nondisclosure of HIV status and/or ART use has been identified previously in other settings, including in other HIV prevention trials and in STI clinics. 6466 Some participants in HPTN 061 also did not agree to HIV testing or did not have samples stored for confirmation of HIV status, and some men with HIV infection were missing CD4 cell count data. Finally, because the current analyses used data collected in a large HIV prevention study, it was not possible to assess all factors or barriers potentially associated with testing.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although HIV testing is not usually performed for individuals with a prior HIV diagnosis, it may occur in clinical settings or clinical trials to confirm self-reported HIV status or to determine HIV status in individuals who are aware of their HIV infection but choose not to disclose this information. 79 …”
mentioning
confidence: 99%